School, family and community in the Environmental Education of the Escuela Bolivariana Las Veritas, Barquisimeto-Venezuela (Biocenosis, 2013)
This study framed in positivist paradigm, descriptive field, aims to determine the school, family and community involved in environmental education Bolivarian The Veritas School, Iribarren Municipality in Barquisimeto, Lara state. The study subjects is made with sixty subjects, they answered three instruments to know if they really involved in environmental education offered at the school. The family answered an instrument consisting of twenty questions with response alternatives yes and no and the community responded a second instrument that also consists of twenty questions with response alternatives yes and no, but instead the instrument was applied to three members of the Common Council, further comprising thirteen questions with response alternatives yes and no. The results indicate that teachers involve family and community and the Common Council in activities related to environmental education, but it is evident that they do not create projects to solve the environmental problems of the community, in addition, it is shown that the family the community and the Community Councils have not participation in the plans and programs set by teachers towards environmental conservation.
Keywords: Non-formal Environmental Education; Andragogy; Community cooperation towards environmental conservation